The Influence of Deep Breathing Techniques and Nature-Based Sound Therapy on Oxygen Saturation and Covid-19 Patients’ Anxiety - Pramita, Senja; Kariasa, I Made; Herawati, Tuti (Fakultas Ilmu-ilmu Kesehatan, 2024)
The treatment for COVID-19 patients with hypoxia is typically limited to invasive and non-invasive oxygenation therapy without any complementary therapy to accelerate improvement in the patient’s health status. The physiological disorders faced by COVID-19 patients also affect their psychology. Anxiety disorders can interfere with physiological processes, such as respiratory processes, aggravating the patient’s oxygenation problems and leading to worsened conditions and death. Therefore, oxygen therapy and pharmacotherapy must be supported by complementary therapies, such as deep breathing. This research aims to investigate the effects of deep breathing relaxation techniques and nature-based sound therapy on the oxygen saturation and anxiety of COVID-19 patients. This study used a quasi-experimental approach with a pretest-posttest control group design approach with 66 samples selected by non-probability sampling. The sample comprised 33 patients in the control group and 33 in the intervention group. The statistical analysis used the Wilcoxon test. The results showed that deep breathing relaxation techniques and nature-based sound therapy increase the patient’s oxygen saturation values and decrease the anxiety score of COVID-19 patients with a p- value of < 0.001. The control group that received the deep breathing relaxation intervention obtained a p-value of <0.001 for increasing oxygen saturation and reducing anxiety levels. Therefore, deep breathing relaxation interventions and nature sound music therapy positively affect COVID-19 patients’ oxygen saturation values and anxiety scores. There are changes in oxygen saturation and anxiety values in the intervention group and control group